Pre-conﬁgured Backup Protection with Limited Resource Sharing in Elastic Optical Networks - Suthaharan, S.; Ratnam, K.; Ragel, R.G. (IEEE 10th International Conference on Industrial and Information Systems (ICIIS'15), 2015)
In this paper, we address the problem of providing survivability in elastic optical networks (EONs). In EONs, unlike the traditional 50 GHz ﬁxed grid, ﬁne granular 12.5 GHz ﬂexgrid is used and the frequency spectrum is used more efﬁciently. For providing survivability, we consider a recently proposed survivability approach known as pre-conﬁgured backup protection with sharing (PBPS) because of its beneﬁts over traditional methods. In PBPS, backup paths can be pre-conﬁgured and at the same time they can share resources. Therefore, both short recovery time and efﬁcient resource usage can be achieved. PBPS has earlier been investigated for ﬁxed-grid and ﬂexgrid (EONs) networks using switch architectures with the power splitting feature of variable optical splitters (VOSs) and combiners. A potential problem in PBPS is power loss due to possible repeated power splitting. To reduce the power loss, ampliﬁers can be used at additional high cost. Alternatively, an approach of limiting backup sharing has been investigated in ﬁxed-grid networks. In this approach the number of power splitting on a backup lightpath at intermediate nodes is limited (to a threshold value) to reduce the total power loss. This approach limits the degree of backup sharing. PBPS with limited backup sharing has not been investigated for ﬂexgrid networks (EONs) and this investigation is the focus of this paper. We carry out this investigation with detailed simulation experiments on different network topologies. Our ﬁndings are as follows. (1) As seen in ﬁxed-grid networks, even with the small number of power splitting, signiﬁcant blocking reduction is seen in EONs. (2) Unlike ﬁxed-grid networks, the blocking performance of PBPS with the small number of power splitting is comparable to the performance associated to unlimited power splitting (unlimited sharing) and, therefore, PBPS with limited sharing is more effective in EONs when compared to ﬁxed grid networks.
Keywords: elastic optical networks; WDM; survivability